Adolescents' enjoyment and effort in class: Influenced by self-directed learning intervals. (December 2022) - Schweder, Sabine; Raufelder, Diana
Abstract: Based on the control-value theory, the present study examined the development and change of enjoyment and effort among adolescents during a school year. The study analyzed 754 adolescent students ( M Age  = 13.56; SD  = 1.2; 49.7% female) who twice participated in a 1-week intervention of self-directed learning (SDL). The results of the bivariate latent neighbor change model showed that—contrary to previous study results—a positive development of enjoyment and effort was generally recorded over the school year and that particularly the two 1-week self-directed learning interventions were beneficial for this increase. Furthermore, the results show that enjoyment and effort were reciprocally linked over time, but only when self-directed learning was experienced first. In other words, by enlarging instruction via self-directed learning intervals, it is possible to counteract the tendency of enjoyment and effort to exhibit a downward spiral. This tendency is especially pronounced during students' entry into secondary school and the onset of adolescence. Highlights: Large data set on instruction suspended by self-directed learning (SDL) (754) Growth of effort and enjoyment is dependent upon multiple intervals of SDL First study of the enjoyment-effort link in instruction that has been enriched by SDL From the second measurement up, it shows strong support for reciprocal relations First experience of SDL is a critical precondition for the enjoyment-effort link